Analisis dampak sektor pariwisata bagi perekonomian warga sekitar kawasan wisata Siblarak Polanharjo Kabupaten Klaten - Husna, Faizah Khotimatul (Journal of Economics Research and Policy Studies, 2022)
Tourism is one of the potential sectors that the regions can develop to establish an area with the help of the government, the community, and the private sector. Apart from impacting regional development, tourism is also expected to bring changes to the community around the tourist area. The Umbul Siblarak Tourism Area is one of the tourist areas built in Klaten Regency. This paper aims to find out the profile of the Umbul Siblarak Tourism Area and the impact of the construction of the Umbul Siblarak Tourism Area on the community, especially in the economic sector. The method used is a descriptive qualitative approach. The data collected came from interview scripts, field notes, observations, and other documents. The results of this study show a positive impact arising from Siblarak tourism. The effect is the existence of business or business opportunities, increased employment or job opportunities for the surrounding community, and improve people's income due to the tourism sector. However, the emergence of the Umbul Siblarak Tourism Area also had a negative impact, namely, damage to the surrounding environment and the existence of promiscuity.